Respuesta :


3.1
x
+
7

7.4
=
1.5
x

6
(
x

3
2
)
Step 1: Simplify both sides of the equation.

3.1
x
+
7

7.4
=
1.5
x

6
(
x

3
2
)

3.1
x
+
7
+

7.4
=
1.5
x
+
(

6
)
(
x
)
+
(

6
)
(

3
2
)
(Distribute)

3.1
x
+
7
+

7.4
=
1.5
x
+

6
x
+
9
(

3.1
x
)
+
(
7
+

7.4
)
=
(
1.5
x
+

6
x
)
+
(
9
)
(Combine Like Terms)

3.1
x
+

0.4
=

4.5
x
+
9

3.1
x

0.4
=

4.5
x
+
9
Step 2: Add 4.5x to both sides.

3.1
x

0.4
+
4.5
x
=

4.5
x
+
9
+
4.5
x
1.4
x

0.4
=
9
Step 3: Add 0.4 to both sides.
1.4
x

0.4
+
0.4
=
9
+
0.4
1.4
x
=
9.4
Step 4: Divide both sides by 1.4.
1.4
x
1.4
=
9.4
1.4
x
=
6.714286

Answer:

x= -1/3

Step-by-step explanation:

In the picture attached. if still doubting the answer, check by Substituing the value of x in the equation given.

Ver imagen dave2110
ACCESS MORE